2021
DOI: 10.3390/su132212773
|View full text |Cite
|
Sign up to set email alerts
|

Applying Data Mining Approaches for Analyzing Hazardous Materials Transportation Accidents on Different Types of Roads

Abstract: With the increase in the demand for and transportation of hazardous materials (Hazmat), frequent Hazmat road transport accidents, high death tolls and property damage have caused widespread societal concern. Therefore, it is necessary to carry out risk factor analysis of Hazmat transportation; predict the severity of accidents; and develop targeted, extensive and refined preventive measures to guarantee the safety of Hazmat road transportation. Based on the philosophy of graded risk management, this study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In order to investigate how the safety and operational characteristics of the traffic will change when AVs are added, traffic micro-simulation appears to be a valuable approach. At the same time, it is necessary to explore data mining and artificial intelligence techniques to find an effective method of understanding traffic behavior at roundabouts [79,80]. This is even more important in the case of AVs, where despite the general trend of safer vehicle movements at roundabouts, there is a risk of some self-driving cars to enter a roundabout without a complete realization of the driving environment.…”
Section: The Role Of Simulationmentioning
confidence: 99%
“…In order to investigate how the safety and operational characteristics of the traffic will change when AVs are added, traffic micro-simulation appears to be a valuable approach. At the same time, it is necessary to explore data mining and artificial intelligence techniques to find an effective method of understanding traffic behavior at roundabouts [79,80]. This is even more important in the case of AVs, where despite the general trend of safer vehicle movements at roundabouts, there is a risk of some self-driving cars to enter a roundabout without a complete realization of the driving environment.…”
Section: The Role Of Simulationmentioning
confidence: 99%
“…Human factors have been the dominant cause of both railroad [47] and truck accidents [48]. Wei et al (2021) found that weather, traffic signals, surface conditions, fatigue, and the time of day have strong associations with hazmat road accidents [49]. Future autonomous aircraft offer the potential to reduce the risk of hazmat transport by eliminating the vehicle operator and distancing the vehicle from populated places and the ground environment.…”
Section: Transporting Dangerous Goodsmentioning
confidence: 99%
“…Previous studies have mostly used association rule mining [18], structural equation modeling, or the Pearson correlation coefcient method to test the correlation between variables, but the Pearson correlation coefcient method usually requires converting variables into dummy variables when dealing with discrete variables, and the more the variable classifcations, the more the dummy variables need to be set up. Pearson's chi-squared test is more suitable for discrete variable correlation analysis than using the Pearson correlation coefcient method, which can reduce the complexity caused by dummy variable settings.…”
Section: Introductionmentioning
confidence: 99%